PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI SOAL CERITA PECAHAN DI KELAS VII MTs ALKHAIRAAT TONDO - Andriani, Vera (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain a description applyingRealistic Mathematic Education (RME) approach able to improving student comprehension class VII MTs Alkhairaat Tondo on word problem fraction matter. This research is a classroom action research, with refers to the design of the research Kemmis dan Mc. Taggart, that is planning, action, observation, and reflection.The results of research indicating applying Realistic Mathematic Education approachwich can understanding improvementstudent to pass trought the steps is to (a) Comprehend the contextualproblematword problemfraction matter, to serve up the techer contectual problem and then student to ask Comprehend the contextual problem, (b) clarifying the contextual problematword problemfraction matter, ait help techer to giving with important signpost to give which can student to direct for Comprehend the problem, (c) compared and cover a lot of ground toÂ the rejoinder, techer to ask student compared and cover a lot of ground toÂ the rejoinder with friends group and then to ask student compared and cover a lot of ground toÂ the rejoinder possession in discussion class(d) conclude, techer to direct student for to drauw aconclusion about problem solve or concept from to learn matter.